Laparoscopic versus open repair of duodenal perforation: a comparative study in tertiary care hospital in Uttarakhand,India - Kumar, Praveen; Kumar, Saurabh; Verma, Ram Kumar; Agarwal, Akshat; Kumari, Rashmi (International Surgery Journal, 2016)
Background: Duodenal ulcer perforation is a common cause of emergency laparotomy. Minimal access surgery is opted with hesitation in most surgical units. The present study was conducted to determine the feasibility of laparoscopic repair of duodenal perforation and to compare it with the conventional open repair in our set-up. Methods: The patients admitted in a single unit of surgery department during a two year period were included in the study. All the patients were admitted in emergency with the diagnosis of duodenal perforation. These were subjected to either laparotomy or laparoscopic repair of duodenal perforation. Results were analyzed and compared. Results: Result analysis indicated laparoscopic approach to be associated with less post-operative complications and morbidity with better patient recovery. Conclusions: We concluded that minimal access approach to duodenal ulcer perforation is safe and should be offered in properly selected cases.